PENGARUH REKRUTMEN, SELEKSI, DAN PENEMPATAN TERHADAP KINERJA KARYAWAN PT. GRAMEDIA, JAKARTA - Caecilia Rosa Permatasari; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2017)
To be able to get loyal customers, PT. Gramedia needs to pay attention on the factors that influence employee performance Moreover, the recent growth of companies in Indonesia engaged in the mass media more and more, so the company must continue to improve the performance of employees so that the company can compete.This research aimed to ascertain the effect of recruitment, selection, and placement on employee performance of PT. Gramedia in Jakarta both simultaneously and partially. The hypothesis was there was an effect of recruitment, selection, and placement, on employee performance of PT. Gramedia in Jakarta both simultaneously and partially. The type of this research was explanatory research with 45 respondents with saturated sampling technique through questionnaire and interview. The data was analyzed using linear regression method with the assistance of SPSS 16.0.The result of this research showed that the recruitment, selection and placement partially positive and significant influence on employee performance. Variable recruitment partially positive and significant influence on employee performance. Variable selection and placement partially positive and significant influence on employee performance. Variable recruitment, selection, and placement simultaneously positive and significant influence on employee performance Based on the result of this research, a conclusion was drawn that customers’ perception on nrecruitment, selection and placement was good. Employee performace of PT. Gramedia were also good. The company was suggested to keep improving the performance of employees in terms of recruitment, selection, and placement are better in line with expectations and needs of the company, so that employees are satisfied and the performance of employees will also increase.